Incidental gallbladder carcinoma in routine cholecystectomy specimens at tertiary care hospital - Kartavya Jatin Mistry; Shilpa Krishnakant Patel; Krishnakant Hargovindbhai Patel; Monaben Nareshbhai Ladwa; Rupal Paresh Mehta (Asian Journal of Medical Sciences, 2023)
Background: Incidental gallbladder carcinoma (IGBC) refers to gallbladder cancer which is not suspected clinically or radiologically and is detected for the first time on histopathological examination (HPE). Aims and Objectives: To find the incidence of IGBC and determine the pathological staging of IGBC accurately as it decides the mode of surgical intervention and thereby increases the quality of life. Materials and Methods: Three years of retrospective study were done from January 2020 to December 2022 at Sheth L. G. General Hospital. Routine histopathological evaluation of 857 such gallbladder specimens was carried out. Fifteen IGBC cases were reported whose pathological staging was done according to American Joint Committee on Cancer and were further analyzed in terms of demographic status, grading, lymph node status, margins, perineural, and lymphovascular invasion. Results: IGBC incidence was 1.75%. Out of 15 IGBC cases, 73% were females. Cholelithiasis was present in 86% of such cases. Gross inspection of all the IGBC-reported specimens revealed thickened gallbladder wall. All cases were adenocarcinoma – pancreaticobiliary type and the most common histologic grade reported was G2. Tumor cells invading the muscularis propria were observed in 7 cases (pT1b), and peri-muscular connective tissue in 7 cases (pT2). Tumor cells invading the serosa were seen in 1 case. (pT3). Conclusion: It is crucial to correctly report the pathologic T stage which determines patient’s survival. The differentiation between pathologic stage pT1a and pT1b should be made cautiously, as this decides the surgical mode of intervention required for increasing the quality of life. In our study, we found the incidence of IGBC to be 1.75%. HPE of all routine cholecystectomy specimens is the gold standard for IGBC detection and is highly recommended irrespective of the radiological diagnosis or macroscopic findings.